The first case of primary hypertrophic osteoarthropathy with soft tissue giant tumors caused by HPGD loss-of-function mutation. Issue 6 (June 2019) - Pang, Qianqian; Xu, Yuping; Qi, Xuan; Jiang, Yan; Wang, Ou; Li, Mei; Xing, Xiaoping; Qin, Ling; Xia, Weibo
Abstract : Background: Primary hypertrophic osteoarthropathy (PHO) is a rare genetic multi-organic disease characterized by digital clubbing, periostosis and pachydermia. Two genes, HPGD and SLCO2A1, which encodes 15-hydroxyprostaglandin dehydrogenase (15-PGDH) and prostaglandin transporter (PGT), respectively, have been reported to be related to PHO. Deficiency of aforementioned two genes leads to failure of prostaglandin E2 (PGE2) degradation and thereby elevated levels of PGE2. PGE2 plays an important role in tumorigenesis. Studies revealed a tumor suppressor activity of 15-PGDH in tumors, such as lung, bladder and breast cancers. However, to date, no HPGD -mutated PHO patients presenting concomitant tumor has been documented. In the present study, we reported the first case of HPGD -mutated PHO patient with soft tissue giant tumors at lower legs and evaluated the efficacy of selective COX-2 inhibitor (etoricoxib) treatment in the patient. Methods: In this study, we summarized the clinical data, collected the serum and urine samples for biochemical test and analyzed the HPGD gene in our patient. Results: A common HPGD mutation c.310_311delCT was identified in the patient. In addition to typical clinical features (digital clubbing, periostosis and pachydermia), the patient demonstrated a new clinical manifestation, a giant soft tissue tumor on the left lower leg which has not been reported in HPGD -mutated PHO patient before. After 6-month treatment with etoricoxib, the patient showed decreased PGE2 levels and improved PHO-related symptoms. Though the soft tissue tumor persisted, it seemed to be controlled under the etoricoxib treatment. Conclusion: This finding expanded the clinical spectrum of PHO and provided unique insights into the HPGD -mutated PHO.